The Role and Synergy of PTKIN and FKUB in Strengthening Interreligious Harmony in Aceh - Safrilsyah, Safrilsyah; Fuad, Fuad; Fuadi, Maimun (Prodi Studi Agama-Agama, 2026)
This study analyzes the roles and patterns of synergy between State Islamic Higher Education Institutions (PTKIN) and the Interfaith Harmony Forum (FKUB) in strengthening interfaith harmony in Aceh. The research employs a qualitative approach using in-depth interviews, participant observation, and institutional document analysis across selected PTKIN and FKUB institutions in Aceh. Data were analyzed through reduction, thematic categorization, and relational pattern interpretation. The findings indicate that PTKIN functions as a center for strengthening religious moderation through curriculum integration, research, and community engagement, while FKUB performs mediative and policy-facilitative roles in managing religious dynamics. Their synergy operates through dialogue forums, moderation training, and community-based collaborative programs. The study concludes that substantive religious harmony is more effectively achieved when PTKIN’s educational function is structurally connected with FKUB’s mediative role and supported by community participation. The research recommends strengthening institutional moderation frameworks within PTKIN and enhancing evidence-based conflict analysis capacity in FKUB